DAMPAK PENDEMI COVID-19 TERHADAP DINAMIKA PEREKONOMIAN WILAYAH DI PROVINSI BALI - Bharata, Ida Bagus Arya Yoga (Jurnal Geografi, 2024)
The mobility limitations imposed by the Covid-19 pandemic have had an impact on dynamic economic sectors that rely on population movement, one of the affected areas is Bali Province. The aims of this research are (1) Mapping the Rate of Regional Economic Growth in Bali Province before and during the Covid-19 Pandemic and (2) Mapping the Classification of Regional Economic Growth in Bali Province before and during the Covid-19 Pandemic. The method used is the Regional Economic Growth Rate and Regional Economic Development Analysis of the Klassen Typology with the main data source being based on GRDP data. In general, the region is developing rapidly which covers six districts, namely Jembrana, Tabanan, Buleleng, Bangli, Karangasem, and Klungkung and the areas that are indeed under economic pressure are the areas in Badung Regency, Denpasar City, and Gianyar Regency both in terms of the rate of economic growth and the level of regional development. where these three areas were significantly affected by the Covid-19 Pandemic.